Social integration - levels and dimensions - Schwinn, Thomas (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
The conceptual proposals on social integration are diffuse and vague. Alarmist diagnoses are contrasted by empirical research results that give an all-clear signal. For an adequate understanding of social integration processes, basic theoretical questions must first be clarified. The specific unit “society” as the point of reference for what is to be integrated is replaced by a constitutional perspective that takes a look at different levels of societization (Vergesellschaftung [Max Weber’s term “Vergesellschaftung” is not easy to translate. I follow Bruun and Whimster’s (in Weber 2012, p. 496) proposal: “societization”.]) and their relationship with one another (social categories, milieus, intermediary organizations, state order, and the global level). Social integration is not identical to a stable and well-organized order. It has value references that set standards for successful integration. However, the extent of cultural integration is no less fraught with conflict than that of social integration. Actors in a certain structural situation resort to such legitimizing values and are thereby confronted with value dilemmas. Sociology is not able to offer ideal states as expressed in conceptual promises of “solidarity” or “cohesion.” Rather, it has a rich knowledge of constellations with different levels of societization in the context of different value relations. This is of central importance for an understanding of the complex processes of integration and disintegration and the role of the social sciences in public discourses on problems of integration.
Gesehen am 04.07.2023
Published online: 23 June 2023